Light‐Driven Crawling of Molecular Crystals by Phase‐Dependent Transient Elastic Lattice Deformation. Issue 26 (15th April 2020) - Gong, Yanjun; Guo, Yongxian; Ge, Fayuan; Xiong, Wei; Su, Jie; Sun, Yang; Zhang, Chuang; Cao, An‐Min; Zhang, Yifan; Zhao, Jincai; Che, Yanke
Abstract: The light‐driven crawling of a molecular crystal that can form three phases, (α, β, and γ) is presented. Laser irradiation of the molecular crystal can generate phase‐dependent transient elastic lattice deformation. The resulting elastic lattice deformation that follows scanning irradiation of a laser can actuate the different phases of molecular crystal to move with different velocity and direction. Because the γ phase has a large Young's modulus (ca. 26 GPa), a force of 0.1 μN can be generated under one laser spot. The generated force is sufficient to actuate the γ‐formed molecular crystals in a wide dimensional range to move longitudinally at a velocity of about 60 μm min −1, which is two orders of magnitude faster than the α and β phases. Abstract : Ahead warp factor one : The force photogenerated by the phase‐dependent transient elastic lattice deformation can actuate molecular crystals to move at a high speed.